Flexibility in adults aged 50 to 86 years participating in a physical activity program - Danielle Ledur Antes; Giseli Minatto; Maryelle Rizzatti Costa; Tânia Rosane Bertoldo Benedetti (Universidade Federal de Santa Catarina, 2013)
An adequate flexibility level is essential to carry out daily activities successfully.This study aimed to verify the effects of a physical activity program over the flexibility of men and women aged 50 to 86 years. A total of 289 participants were evaluated from March 2009 to March 2011. The physical activity program included 60-minute gym classes three times a week. The physical capacities most exercised were resistance strength, equilibrium, flexibility, coordination, aerobic resistance, and muscle strength and relaxation. Flexibility was measured with the sit and reach test. The descriptive analysis and paired t test were performed with a 5% significance level. We observed a significant reduction in women's flexibility (p < 0.001) during the physical activities practice period. This reduction was more significant in 2009 than in 2010 (p < 0.001). During the recess periods, there was a significant decline in flexibility (p < 0.001) for both sexes. From 2009 to 2010, however, there was a difference in reduction only among women, with a less significant reduction from 2010 to 2011 when compared to the 2009-2010 period. We concluded that both men's and women's flexibility levels reduced, but men's levels reduced only during recess, while women's levels reduced during recess and practice periods. A regular physical activity practice may contribute to the development and/or maintenance of flexibility levels in adults over 50 years old.